Differentiable structures on a generalized product of spheres - Samuel Omoloye Ajala (International Journal of Mathematics and Mathematical Sciences)
In this paper, we give a complete classification of smooth structures on a generalized product of spheres. Ihe result generalizes our result in [1] and R. de Sapio's result in [2].